A STUDY ON THE ABILITY OF THE SECOND YEAR STUDENTS OF SMPN 5 TELUK KUANTAN IN COMPREHENDING DESCRIPTIVE TEXTS - Yanhuda, Ade Widiyastuti; Afrianto, Afrianto; Azhar, Fadly (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This study is aimed to find out the ability of the second year students of SMPN5TelukKuantan in comprehending descriptive texst. It is a descriptive research which was carried at from July-August 2018. The population were 123 students, their characters are homogeneous in terms of academic achievementand age factors. The cluster random strategies technique was choosen due to that every class has equal opportunity to be a sample group. The sample consisted of two categories, try out class (VIII C) and sample class (VIII A)The data in this research is quantitative data. The students was give a multiple coice test, in which they asked to answer the question. The test focused on the material of descriptive text. The subjects require choosing the best answer of the provide questions. Five texts used in the instruments. Each text consisted of six item multiple choices. There are 30 items that included in this test. The duration time doing the test is 60 minutes. The test constructed by referring to the components of reading comprehension is finding main ideas, finding factual information, finding references, finding the maning of difficult words, and finding restatement. The data were analyzed by calculating the students’ scores, classified into five level mastery, such as very poor, poor, mediocre, good and excellent. Based on the analyzing data of this research, it was found that the students’ ability in comprehending descriptive text at second year students of SMPN 5TelukKuantan was in good level. Meanwhile, the mean score of the whole students’ scores was 67.4. The implication of the finding is that the second year students of SMPN 5 TelukKuantan is able enough at comprehend descriptive texts.Keyword : students’ ability, comprehending descriptive texts